Proliferation and Morphogenesis of the Endoplasmic Reticulum Driven by the Membrane Domain of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase in Plant Cells. Issue 3 (26th May 2015) - Ferrero, Sergi; Grados-Torrez, Ricardo Enrique; Leivar, Pablo; Antolín-Llovera, Meritxell; López-Iglesias, Carmen; Cortadellas, Nuria; Ferrer, Joan Carles; Campos, Narciso
Abstract : The membrane domain of 3-hydroxy-3-methylglutaryl CoA reductase contributes to the morphogenesis of the endoplasmic reticulum. Abstract: The enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) has a key regulatory role in the mevalonate pathway for isoprenoid biosynthesis and is composed of an endoplasmic reticulum (ER )-anchoring membrane domain with low sequence similarity among eukaryotic kingdoms and a conserved cytosolic catalytic domain. Organized smooth endoplasmic reticulum (OSER ) structures are common formations of hypertrophied tightly packed ER membranes devoted to specific biosynthetic and secretory functions, the biogenesis of which remains largely unexplored. We show that the membrane domain of plant HMGR suffices to trigger ER proliferation and OSER biogenesis. The proliferating membranes become highly enriched in HMGR protein, but they do not accumulate sterols, indicating a morphogenetic rather than a metabolic role for HMGR. The N-terminal MDVRRRPP motif present in most plant HMGR isoforms is not required for retention in the ER, which was previously proposed, but functions as an ER morphogenic signal. Plant OSER structures are morphologically similar to those of animal cells, emerge from tripartite ER junctions, and mainly build up beside the nuclear envelope, indicating conserved OSER biogenesis in high eukaryotes. Factors other than the OSER -inducing HMGR construct mediate the tight apposition of the proliferating membranes, implying separate ER proliferation and membrane association steps. Overexpression of the membrane domain of Arabidopsis ( Arabidopsis thaliana ) HMGR leads to ER hypertrophy in every tested cell type and plant species, whereas the knockout of the HMG1 gene from Arabidopsis, encoding its major HMGR isoform, causes ER aggregation at the nuclear envelope. Our results show that the membrane domain of HMGR contributes to ER morphogenesis in plant cells.